Frequency of microalbuminuria in patients below 18 years of age with type 1 diabetes mellitus - Vega Torrejon, Brenda (2025)
Type 1 diabetes mellitus is more frequent in kids, particularly among those younger than five years of age, which is concerning because complications are present at an earlier age. Microalbuminuria is the primary indicator of kidney injury and can be used to monitor disease progression. Objective: To determine the frequency of microalbuminuria among type 1 diabetic patients younger than 18. Methods: A retrospective, observational, and multicenter study was conducted from 2018-2020 in two hospitals in Lima, the National Pediatric Institute and Hospital Cayetano Heredia. We reviewed 119 clinical charts and included 73 that fulfilled the recruitment criteria. Statistical analysis was carried out with STATA, version 18. Results: the frequency of microalbuminuria was 20.55% (n=15); 60% (n=9) were females; 66.67% (n=10) were adolescents; median age was 12 years; median disease duration was 3.8 years, and the most frequent comorbidity was dyslipidemia (46.7%). Conclusions: The frequency of microalbuminuria was 20.55%.